2017
DOI: 10.1111/aogs.13206
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocalc: implementation and uptake of personalized postpartum venous thromboembolism risk assessment in a high‐throughput obstetric environment

Abstract: Our electronic, score-based VTERA tool provides a highly effective mechanism for rapid assessment of individual postpartum venous thromboembolism risk in a high-throughput environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Because of the small size of the nonstudy cohort, these differences are unlikely to have influenced the prevalence of these risk factors to an important degree. Second, we have previously reported on the potential for minor misclassifications in VTE risk factors relating to age, parity, delivery outcome, gestational age, and delivery mode, affecting an estimated 14% of risk assessments completed at our institution . Although the availability of information from the hospital's obstetric management system allows us to correct all inaccuracies in relation to these specific misclassifications, there remains a small potential for residual inaccuracies, primarily arising from the omission of VTE risk factors from the risk assessment, and subsequent underestimation of prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the small size of the nonstudy cohort, these differences are unlikely to have influenced the prevalence of these risk factors to an important degree. Second, we have previously reported on the potential for minor misclassifications in VTE risk factors relating to age, parity, delivery outcome, gestational age, and delivery mode, affecting an estimated 14% of risk assessments completed at our institution . Although the availability of information from the hospital's obstetric management system allows us to correct all inaccuracies in relation to these specific misclassifications, there remains a small potential for residual inaccuracies, primarily arising from the omission of VTE risk factors from the risk assessment, and subsequent underestimation of prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum VTE risk assessment is carried out using an electronic risk assessment tool, termed “Thrombocalc.” Full details of this risk assessment process and an image of the risk assessment tool are previously published . In brief, Thrombocalc allows for standardized assessment of postpartum VTE risk in each individual woman at the point of care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr O’Shaughnessy of the Rotunda Hospital, Dublin, Ireland, presented pilot data evaluating the impact of systematic electronic VTE risk assessment in all postpartum women combined with a strong positive campaign to increase VTE awareness among multidisciplinary colleagues on VTE prevention strategies in a large maternity hospital . Introduction of these measures resulted in an increase in use of risk‐appropriate pharmacological thromboprophylaxis (RA‐TPX) from 68% to 89% ( P < 0.001).…”
Section: Reducing the Risk Of Vte In Pregnancymentioning
confidence: 99%
“…The reality of performing VTE risk assessment can be incredibly challenging, particularly in the often chaotically busy environment of the delivery suite or postnatal ward. However, we have recently demonstrated that, when this complex, multistep process is streamlined and tailored to this extremely busy environment with intense multidisciplinary stakeholder involvement, systematic risk assessment of a very high proportion of women is feasible …”
Section: Vte Awareness During Pregnancy and The Importance Of Risk Asmentioning
confidence: 99%